Contributions of Decision Making Theory to comprehensive medical attention. - Luis Alberto Corona Martinez; Mercedes Fonseca Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Decision Making Theory contributes many useful elements for General Comprehensive Doctors, associated with their function of integral attention, mainly related with treatment. In this article we present as core elements: the need for logic to make decisions, the usefulness of programmed and non-programmed decisions concepts and the importance of make individual decisions using determination factors.